Sport across Asia politics, cultures, and identities - Bromber, Katrin; Krawietz, Birgit; Maguire, Joseph (Routledge research in sport, culture and society, 2013)
This book is designed to reflect both our current knowledge regarding sport, globalisation and '"encounters" with several important "post-colonial" or non-western societies and to draw together scholars from a range of different disciplines. Case studies of cultural encounters in Central, South-East Asia, Asia Minor and the Arabian peninsula capture the paradoxical processes of emulation, resistance and transformation that are at work in the diffusion and development of "sport" and body cultures. These case studies bring together insights from anthropology, cultural studies, geography, history, law, sociology, various area and post-colonial studies.